Efektifitas Metode Fernald Untuk Meningkatkan Kemampuan Membaca Pada Anak Anggota Polri Penyandang Disleksia - koeswoyo dwi; Rudi Cahyono (Jurnal Litbang Polri, 2022)
ABK or Children with Special Needs are individuals who are less able to manage, and carry out certain activities in general, without always showing certain mental, emotional and physical disabilities. There are various types of ABK, including Dyslexia, ADHD, Autism, Down Syndrome, etc. Dyslexia is difficulty reading, spelling, writing, and difficulty in interpreting or recognizing the structure of words that have an effect on the learning process or learning disorders. The causes of dyslexia are neurological and genetic disorders. In this study, the subjects studied by the researchers were assessed in the form of interviews, observations, WISC, VSMS, SPM and informal reading tests, and it was found that the subjects had dyslexia. The method used in this research is qualitative. The researcher provides an intervention in the form of teaching using the Fernald method, this method is a multisensory approach for teaching reading, writing, and spelling to children. The results of this intervention were carried out for 10 sessions (pretest and posttest) and it was found that this method was effectively used for dyslexic children.